2019
DOI: 10.4174/astr.2019.96.5.209
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a resident night float system in a surgery department in Korea for 6 months: electronic medical record-based big data analysis and medical staff survey

Abstract: Purpose To evaluate superiority of a night float (NF) system in comparison to a traditional night on-call (NO) system for surgical residents at a single institution in terms of efficacy, safety, and satisfaction. Methods A NF system was implemented from March to September 2017 and big data analysis from electronic medical records was performed for all patients admitted for surgery or contacted from the emergency room (ER). Parameters including vital signs, mortality, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 19 publications
4
22
0
Order By: Relevance
“…Also, there were some doubts that the NF system may reduce the quality of residents' education [8] as well as the education opportunities due to decrease interactions and conferences during the NF system [17]. We found that education experiences and opportunities to learn procedures among pediatrics residents were in favor of the NF shifts.…”
Section: Discussion and Literature Reviewmentioning
confidence: 76%
See 3 more Smart Citations
“…Also, there were some doubts that the NF system may reduce the quality of residents' education [8] as well as the education opportunities due to decrease interactions and conferences during the NF system [17]. We found that education experiences and opportunities to learn procedures among pediatrics residents were in favor of the NF shifts.…”
Section: Discussion and Literature Reviewmentioning
confidence: 76%
“…Several studies tested the impact of the application of the Night Float (NF) system. In Korea in 2017, the NF system was implemented in a research study on surgery and emergency residents [8]. In Singapore, it was implemented on interns of internal medicine department [6].…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the regulation was implemented and teaching hospitals in Korea were given a hours; and minimum off-duty time between duty shifts should be guaranteed 10 hours. Despite the implementation of this regulation, there has been a report evaluating the superiority of a night float system with regard to duty hours [5].…”
Section: Introductionmentioning
confidence: 99%